Labor Market Risk in Germany - Tom Krebs; Yao Yao (Institute for the Study of Labor (IZA), 2016)
This paper uses annual data drawn from the GSOEP to estimate individual earnings risk (labor market risk) in Germany for the period 1983-2012. The econometric specification of the earnings process allows for transitory shocks and permanent shocks to individual earnings. We find that both the transitory component and the permanent component of earnings risk have been rising in West Germany in the 1990s and have remained at elevated levels in the 2000s. In contrast, labor market risk in East Germany did not rise. These findings are robust to different sample selection criteria and changes in the specification of the earnings process. We provide a simple welfare calculation that suggests that the negative welfare consequences of the observed rise in the permanent component of earnings risk in West Germany are substantial. We argue that the time series evidence is not consistent with the view that international trade integration has been a main driver of the observed rise in labor market risk in West Germany.
Keywords: J31; D52; 330; labor market risk; Germany